Answer:
Make x=0, therefore y=-2+(-1x0)
Explanation:
x| y= -2-1x | (x,y)
--------------------------
0| y= -2-1= -3•0=0 | (0,0)
---------------------------
1| y= -2-1= -3•1= -3 | (1,-3)
---------------------------
2| y= -2-1= -3•2= -6 | (2,-6)
So now you have your points, (0,0), (1,-3), (2,-6) . You can always make it easier by just
drawing out a table like above. Just replace the x with any number you want and work out the problem y = -2-1x . Then with the number you chose, replace the x in the problem so you can solve it.